Room-temperature VOC sensing and adsorption behavior of electrochemically synthesized ZnO nanorods under light and non-illuminated conditions - Sahin, Ayse Nur; Altindal, Ahmet; Ozdemir, Zeynep Guven (SPRINGER, 2025)
Zinc oxide (ZnO) nanorods (NRs) have emerged as a promising material for gas sensing applications due to their high surface area, good chemical stability, and unique electronic properties. This study covers the synthesis, characterization, and application of ZnO NRs for detecting volatile organic compounds' (VOCs) vapors, particularly ammonia (NH3), under room-temperature and light illumination conditions. ZnO NRs were synthesized by electrochemical deposition method and characterized using XRD, SEM, UV-Vis spectroscopy, and FTIR techniques. The sensing performance of ZnO NRs was evaluated for various VOCs vapors, including acetone, isopropanol (IPA), ethanol, methanol, and butanol vapors at concentrations ranging from 50 to 350 ppm. The ZnO NR sensors demonstrated good selectivity toward ammonia vapor, with a response 2440 times higher than baseline at 250 ppm. Under UV illumination, the sensors exhibited enhanced photocurrent generation, improving detection sensitivity for ammonia. Adsorption kinetics were also analyzed, revealing that the Elovich model best describes the adsorption process due to its heterogeneous surface energy assumption. The results show that ZnO NR sensors are suitable for room-temperature light-activated, high-sensitivity, low-cost sensor platforms. Furthermore, comparisons with previous studies demonstrate the superiority of this sensor in terms of performance. These findings highlight the potential of ZnO NRs as effective gas sensors, especially for ammonia detection, paving the way for advanced environmental and industrial monitoring systems.
Keywords: ELOVICH EQUATION; GAS SENSORS; THIN-FILMS; KINETICS; PERFORMANCE; Engineering; Materials Science; Physics